Organization of work on linguistic and literary-educational terminology as a means of forming didactic competence of future teachers of philological specialties - Мішеніна, Т. М. (Pedagogy of Higher and Secondary Education, 2012)
Misheninа T.M. Organization of work on linguistic and literary-educational terminology as a means of forming didactic competence of future teachers of philological specialties. Psychological descriptions of educational dialogue and its features which expose the specific of dialogue organization in educational process, show its possibilities in bringing up personality sphere of students as well as in developing their professionally oriented speech competence in the process of foreign languages learning are considered in the article.